Loneliness, Emotion Dysregulation, and Internalizing Symptoms During Coronavirus Disease 2019: A Structural Equation Modeling Approach - Velotti, Patrizia; Rogier, Guyonne; Beomonte Zobel, Sara; Castellano, Rosetta; Tambelli, Renata (Frontiers in Psychiatry, 2021)
Background: The aim of our study was to test the hypotheses that an increased level of loneliness experienced during COVID -19 confinement was predictive of internalizing symptoms and that this pathway was mediated by emotion dysregulation levels. Methods: To reach this aim, we performed an online longitudinal survey recruiting 1330 participants at Time 1 (at the beginning of the lockdown) and 308 participants at Time 2 (few days before the end of the lockdown). All filled out a set of questionnaires: demographic data, UCLA Loneliness scale, Difficulties in Emotion Regulation Scale - 18 items and Depression Anxiety and Stress Scale - 21 items. Hypotheses were tested using Structural Equation Modelling in two steps and controlling for Age. First, hypotheses were tested on cross-sectional data. Then, a cross lagged panel analysis was performed on longitudinal data. Results: Models obtained a good fit and evidenced the predictive role of loneliness levels on the three outcomes (i.e. depression, anxiety and stress). Moreover, we found that emotion dysregulation levels partially mediated the longitudinal relationship between loneliness and both depression and stress but not between loneliness and anxiety levels. Conclusions: This study points out that a central goal of clinical intervention could be the ability to regulate negative emotional states.